2016
DOI: 10.1021/acs.inorgchem.6b00242
|View full text |Cite
|
Sign up to set email alerts
|

K8(K5F)U6Si8O40: An Intergrowth Uranyl Silicate

Abstract: Single crystals of K8(K5F)U6Si8O40 were grown from a mixed alkali halide flux. K8(K5F)U6Si8O40 is the first intergrowth uranyl silicate, being composed of alternating slabs related to two previously reported uranyl silicates: Cs2USiO6 and [Na9F2][(UO2)(UO2)2(Si2O7)2]. It exhibits intense luminescence, which is influenced by the [(UO2)2O] dimers present in the structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 33 publications
4
24
0
Order By: Relevance
“…11 Interestingly, in the case of uranyl saltinclusion compounds, these phases exhibit intense lumines-cence at room temperature, whereas in uranyl oxides the luminescence is typically thermally quenched. 20,21 Similar behavior has been observed for uranyl oxychlorides 22,23 and is likely due to the softening of the vibrational modes by the halide anion. Besides luminescence, many salt-inclusion phases are noncentrosymmetric, making them potential second harmonic generation materials.…”
Section: ■ Introductionsupporting
confidence: 69%
“…11 Interestingly, in the case of uranyl saltinclusion compounds, these phases exhibit intense lumines-cence at room temperature, whereas in uranyl oxides the luminescence is typically thermally quenched. 20,21 Similar behavior has been observed for uranyl oxychlorides 22,23 and is likely due to the softening of the vibrational modes by the halide anion. Besides luminescence, many salt-inclusion phases are noncentrosymmetric, making them potential second harmonic generation materials.…”
Section: ■ Introductionsupporting
confidence: 69%
“…The zur Loye group has focused on synthesizing novel uranium-containing SIMs via alkali halide fluxes and while the majority of these have been prepared from ACl-AF eutectics, some success was achieved with the use of ABI fluxes. A novel intergrowth uranyl silicate, K 8 (K 5 F)U 6 Si 8 O 40 , was grown from a KF-KBr flux (Morrison et al, 2016b ), and unlike many other uranyl compounds, K 8 (K 5 F)U 6 Si 8 O 40 was found to exhibit intense luminescence behavior possibly attributable to the salt-inclusion. Similarly, a KF-KBr flux was used to prepare [KK 6 Br 0.6 F 0.4 ][(UO 2 ) 3 (Ge 2 O 7 ) 2 ] (Juillerat et al, 2018 ) in a study to explore the adaptability of the uranyl germanate SIM framework.…”
Section: Salt-inclusion Materialsmentioning
confidence: 99%
“…An increase of the U:Si ratio is also related to a change of linkage mode between U and Si polyhedra, from edge-to corner-sharing. The high U:Si is characteristic for the synthetic compounds [23][24][25][26][27][28][29], which will not be mentioned in the following text. The approach concerning secondary-building units (SBUs)is a useful tool for highlighting differences in mineral groups mentioned above.…”
Section: Mineralogy and Crystallography Of Natural Uranyl Silicatesmentioning
confidence: 99%
“…Infrared and Raman spectroscopy data for natural uranyl silicates have been reported by [21] and also recently by a thorough review of Raman spectroscopy of uranyl minerals and phases [22]. With increased attention many synthetic uranyl silicate compounds have been synthesized, usually with crystal chemistry divergent from the natural ones [23][24][25][26][27][28][29], and also both experimental [30][31][32] and theoretical studies [33,34] have been undertaken in order to determine the thermodynamic properties of uranyl silicate minerals.…”
Section: Introductionmentioning
confidence: 99%